2020
DOI: 10.1111/ijlh.13397
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of ATIC in multiple myeloma tissues based on tissue microarray and gene microarrays

Abstract: Purpose Multiple myeloma (MM) is characterized by the malignant proliferation of plasma cells, which produce a monoclonal immunoglobulin protein. The role of 5‐aminoimidazole‐4‐carboxamide ribonucleotide formyltransferase/IMP cyclohydrolase (ATIC) has not yet been well studied in the area of MM. Thus, in the current study, we sought to examine the expression levels, including mRNA and protein levels of ATIC in MM. Methods Multiple myeloma microarray and RNA‐seq data were screened from the SRA, GEO, ArrayExpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…ATIC is a critical bifunctional enzyme that catalyzes the final 2 steps of the purine de novo biosynthetic pathway [ 22 ]. Higher ATIC is associated with the progression of several cancers, such as ATIC hepatocellular cancer [ 23 ], multiple myeloma tissues [ 24 ] and lung adenocarcinoma [ 25 ]. It is clarified that ATIC-mediated assembly of the multienzyme purinosome complex is driven by hypoxia via HIF-1 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…ATIC is a critical bifunctional enzyme that catalyzes the final 2 steps of the purine de novo biosynthetic pathway [ 22 ]. Higher ATIC is associated with the progression of several cancers, such as ATIC hepatocellular cancer [ 23 ], multiple myeloma tissues [ 24 ] and lung adenocarcinoma [ 25 ]. It is clarified that ATIC-mediated assembly of the multienzyme purinosome complex is driven by hypoxia via HIF-1 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“… 22 The abnormal expression of ATIC is closely related to the prognosis of hepatocellular carcinoma patients and can cause significant changes in the proliferation and migration of hepatocellular carcinoma cells. 23 Other studies have also shown that the abnormal expression of ATIC is closely related to the occurrence of various diseases, including multiple myeloma, 24 lung cancer, 25 lymphoma, 26 etc. We found that ATIC gene was associated with VSD in the Chinese Tibetan population, and it was associated with ASD, ventricular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that ATIC activates mTOR-S6 kinase 1 signaling and consequently stimulates the proliferation and migration of oncotic cells [ 25 ]. Furthermore, the gene has been associated with autophagy and an increased risk of developing HCC [ 26 ], lung cancer [ 27 ], and multiple myeloma [ 28 ].…”
Section: Discussionmentioning
confidence: 99%